The dolabellane diterpenes as potential inhibitors of the SARS-CoV-2 main protease: molecular insight of the inhibitory mechanism through computational studies. Issue 62 (10th December 2021) - Aminah, Nanik Siti; Abdjan, Muhammad Ikhlas; Wardana, Andika Pramudya; Kristanti, Alfinda Novi; Siswanto, Imam; Rakhman, Khusna Arif; Takaya, Yoshiaki
Abstract : An investigation on dolabellane derivatives to understand their potential in inhibiting the SARS-CoV-2 main protease (3CL pro ) using an in silico approach. Abstract : An investigation has been carried out on natural products from dolabellane derivatives to understand their potential in inhibiting the SARS-CoV-2 main protease (3CL pro ) using an in silico approach. Inhibition of the 3CL pro enzyme is a promising target in stopping the replication of the SARS-CoV-2 virus through inhibition of the subsite binding pocket. The redocking process aims to determine the 3CL pro active sites. The redocking requirement showed a good pose with an RMSD value of 1.39 Å. The combination of molecular docking and MD simulation shows the results of DD13 as a candidate which had a good binding affinity (kcal mol −1 ) to inhibit the 3CL pro enzyme activity. Prediction of binding free energy (kcal mol −1 ) of DD13 using the Molecular Mechanics-Poisson Boltzmann/Generalized Born Surface Area (MM-PB/GBSA) approach shows the results Δ G bind(MM-GBSA) : −52.33 ± 0.34 and Δ G bind(MM-PBSA) : −43.52 ± 0.42. The key residues responsible for the inhibition mechanism are Hie41, Ser46, Met49, Asn142, Cys145, Hie163, Met165, and Gln189. Additionally, pharmacokinetic prediction recommended that DD13 had promising criteria as a drug candidate. The results demonstrated in this study provide theoretical information to obtain a potential inhibitor against the SARS-CoV-2 main protease.